The K+ channel TASK1 modulates β‐adrenergic response in brown adipose tissue through the mineralocorticoid receptor pathway. Issue 2 (2nd November 2015) - Pisani, Didier F.; Beranger, Guillaume E.; Corinus, Alain; Giroud, Maude; Ghandour, Rayane A.; Altirriba, Jordi; Chambard, Jean‐Claude; Mazure, Nathalie M.; Bendahhou, Saïd; Duranton, Christophe; Michiels, Jean‐François; Frontini, Andrea; et al.
Abstract : Brown adipose tissue (BAT) is essential for adaptive thermogenesis and dissipation of caloric excess through the activity of uncoupling protein (UCP)‐1. BAT in humans is of great interest for the treatment of obesity and related diseases. In this study, the expression of Twik‐related acid‐sensitive K + channel (TASK)‐1 [a pH‐sensitive potassium channel encoded by the potassium channel, 2‐pore domain, subfamily K, member 3 ( Kcnk3 ) gene] correlated highly with Ucp1 expression in obese and cold‐exposed mice. In addition, Task1 ‐null mice, compared with their controls, became overweight, mainly because of an increase in white adipose tissue mass and BAT whitening. Task1 –/– ‐mouse‐derived brown adipocytes, compared with wild‐type mouse‐derived brown adipocytes, displayed an impaired β3‐adrenergic receptor response that was characterized by a decrease in oxygen consumption, Ucp1 expression, and lipolysis. This phenotype was thought to be caused by an exacerbation of mineralocorticoid receptor (MR) signaling, given that it was mimicked by corticoids and reversed by an MR inhibitor. We concluded that the K + channel TASK1 controls the thermogenic activity in brown adipocytes through modulation of β‐adrenergic receptor signaling.—Pisani, D. F., Beranger, G. E., Corinus, A., Giroud, M., Ghandour, R. A., Altirriba, J., Chambard, J.‐C., Mazure, N. M., Bendahhou, S., Duranton, C., Michiels, J.‐F., Frontini, A., Rohner‐Jeanrenaud, F., Cinti, S., Christian, M., Barhanin, J., Amri, E.‐Z. The K + channel TASK1 modulates β‐adrenergic response in brown adipose tissue through the mineralocorticoid receptor pathway. FASEB J. 30, 909–922 (2016). www.fasebj.org